Trade in Sub-Saharan Africa and Opportunities for Low Income Countries - Manners, P.; Behar, A. (Washington, DC: World Bank, 2012)
Sub-Saharan African countries are further from economic markets than most other regions in the world. This largely reflects the small size of economic markets within the Sub-Saharan region. Despite its distance to the major economic markets, more than 80 per cent of Sub-Saharan trade is outside of its own region. Using a gravity model, such a trade pattern would be expected. In fact, Sub-Saharan African countries typically under-export to countries outside their own region, while they export about as much to countries within their region as would be expected, given their economic size. There is a pattern of increasing regionalization of trade over the past 25 years. The pattern of Sub-Saharan trade is not easily explained by colonial relationships, language barriers, internal geography or logistics, despite all these variables being highly significant in explaining bilateral trading relationships. It may instead reflect tariff and non-tariff barriers, although this conclusion is not tested within this paper.